Mentoring Keagamaan Siswa SMP Muhammadiyah Terpadu Kota Bengkulu - Noveriyanto, Noveriyanto; Fadhillah, Sarrah Kurnia; Winarti, Een (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2023)
Religious mentoring is a means of forming Muslim personalities and inculcating moral values. This mentoring activity is routinely carried out by teachers at the Integrated Muhammadiyah Middle School in Bengkulu City. The purpose of this research is to analyze the process of implementing mentoring activities carried out on students of the Integrated Muhammadiyah Junior High School in Bengkulu City. This study uses a qualitative approach with data collection techniques, namely observation, interviews, documentation. The data obtained by the researcher is then categorized and collected from research questions, then the researcher can conclude the research and use SWOT analysis. The research subjects were all students of the Integrated Muhammadiyah Middle School. From the results of the research that in the process of carrying out these mentoring activities students routinely listen to studies or lectures, facilitate students' interests and talents, train students to be brave and confident, motivate them to be able to be responsible, and interact more with the Al-Qur'an. Mentoring activities for students of the Integrated Muhammadiyah Middle School in Bengkulu City are carried out in groups, namely one group consisting of 5-10 students with 1 (one) mentor each, this activity begins with reading Bismillah together and continues with reading Al-Fatihah , then provision of mentoring material by each coach. Besides that, this activity can also help students (mente) in memorizing prayer readings, asmaul husna, even short surahs, then with this mentoring activity it also helps in increasing self-confidence in students (mente).